GAMBARAN TEKANAN DARAH INTRAOPERASI PADA PASIEN BEDAH MAYOR ORTOPEDI DENGAN REGIONAL ANESTESI - Adji Wicaksono; Angelita Debora; Fery Septiawan; Stein M.A.A.Q. Amsikan; Romi Rizkiansyah; Ganik Sakitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Background: Major orthopedic surgery has the potential to cause changes in hemodynamics during surgery. The regional anesthesia technique known as Subarachnoid Block (SAB) can trigger hypotension due to sympathetic blockade, so blood pressure monitoring is essential. Objective: To understand the intraoperative blood pressure panorama in major orthopedic surgery using the SAB method. Methods: A descriptive observational study was conducted on ten major orthopedic surgery patients with SAB regional anesthesia at Dr. Soedono Madiun Regional Hospital between January and February 2026. Parameters analyzed included intraoperative blood pressure graphs. Results: Most patients experienced a reduction in blood pressure in the early stages of surgery due to sympathetic blockade. However, these changes remained within clinically tolerable limits and could be managed with close hemodynamic monitoring. Conclusion: SAB regional anesthesia in major orthopedic surgery showed relatively maintained hemodynamic stability with mild to moderate hypotension that can be managed well with good preanesthetic and optimal intraoperative monitoring.